MEDIASI KEPUASAN PELANGGAN DALAM HUBUNGAN CUSTOMER EXPERIENCE DAN MINAT BELI ULANG DI AMING COFFEE PONTIANAK - Octaviani, Dina; Ekawati, Ekawati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2023)
This study aims to determine the effect of customer experience, sales promotion, customer satisfaction and repurchase interest in Aming Coffee. The research was conducted in Pontianak City, using a sample size of 100 people. The sampling technique used was Non-Probability Sampling, with the sampling method being Purposive. Data was obtained by distributing online questionnaires and data analysis methods with SEM-PLS using WarpPLS 6.0 software. The results of this study indicate that customer experience has a positive and significant effect on customer satisfaction. Customer experience, sales promotion, and customer satisfaction positively and significantly affect repurchase intention with a coefficient value. Customer satisfaction can dramatically mediate the effect of customer experience on repurchase intention. Aming Coffee is expected to provide and improve better service to its customers to create the customer experience expected by customers and deliver sales promotions that align with consumer expectations so that they impact consumer repurchase interest in Aming Coffee in Pontianak.